Temperate performance benefits after heat, but not combined heat and hypoxic training - McCleave, E. L.; Slattery, K. M.; Duffield, R.; Saunders, P. U.; Sharma, A. P.; Crowcroft, S. J.; Coutts, A. J. (Medicine & Science in Sports & Exercise, 2017)
Purpose: Independent heat and hypoxic exposure can enhance temperate endurance performance in trained athletes, although their combined effects remain unknown. This study examined whether the addition of heat interval training during "live high, train low" (LHTL) hypoxic exposure would result in enhanced performance and physiological adaptations as compared with heat or temperate training.